Metode Tahfizh Al-Qur’an Bagi Pelajar dan Mahasiswa - al Maududi, Abul A’la; Mujahidin, Endin; Hafidhuddin, Didin (Ta'dibuna: Jurnal Pendidikan Islam, 2014)
The Qur’an is God’s holy words which is kept its originality until Doomsday; maintained through Qur’anic memorizing that exists in the heart of the believers (Mu’minin). The students’ time both in high school and university is the golden time ? the time that should be maintained well because it has big potency to be memorizer of Qur’an and the originality of Qur’an will be save. The activity of memorizing Qur’an is common obligation for the Muslim (fardhukifayah) and one of the important matters. The main goal of this research is: 1) to know and analysis method of Qur’anic memorizing in the institution of Qur’an El Fawaz (Rumah al-Qur’an). 2) the main factors that can make it easier to memorize the Qur'an and the inhibiting factors for the students of high school and university, and 3) effective method of Qur’anic memorizing for the students of high school and university.This research is conducted by using qualitative and quantitative approach reinforced with the basis of phenomenology and the method of research is using research action. The data is acquired through primary data; participative observation, deep interview, questioner, evaluation techniques and secondary data; basic skill test which covers (intellectual intelligence test, concentrations, memory, commitment to the task), library research, and documentation study. The findings of the research are: 1) the main factors that can make it easier to memorize the Qur'an for the students; heartily intention; high motivation; intellectual intelligence; using Rasm Utsmani; existence of supervisor and increasing love of Qur’anic memorizing. 2) the inhibiting factors of Qur’anic memorizing for the students; being busy with the routine activities (work); weak motivation; low intellectual intelligence; immoral activities, impatient; not feeling the pleasure of Qur’an. 3) the effective method of memorizing Qur’an for the students; reading Qur’an, five parts (juz) every day, listening the reading of Qur’an through multimedia, talaqqi syafahiyyah with the supervisor, memorizing Qur’an one day one page after Shubuh prayer by dividing in three parts; correlating verses by verses, page by page, surah by surah, and reviewing Qur’an after Magrib prayer and before shubuh prayer with slow reading (al-Tartil) routinely. The conclusion of this research can be pointed that the method application of Qur’anic memorizing in the institution of Qur’an El Fawaz (Rumah al-Qur’an) is effective and there are several key factors and inhibitors in memorizing the Qur'an for students and effective method for memorizing the Qur'an for students without disrupting the routine of teaching and learning activities for students. Keywords: Mahasiswa, Metode, Tahfidz al Qur’an, Pelajar,